Oxidation behaviour of an intermetallic Ti–Al–Cr–Zr bond coat on a γ–TiAl based TNB alloy with 7YSZ thermal barrier coating. (4th May 2018) - Laska, Nadine; Watermeyer, Philipp; Koliotassis, Lisa; Braun, Reinhold
Abstract: Intermetallic titanium aluminide alloys are attractive light-weight materials for high temperature applications in automotive and aero engines. The development of γ -TiAl alloys over the past decades has led to their successful commercial application as low pressure turbine blades. The operating temperatures of γ -TiAl based alloys are limited by deterioration in strength and creep resistance at elevated temperatures as well as poor oxidation behaviour above 800 °C. Since improvement in oxidation behaviour of γ -TiAl based alloys without impairing their mechanical properties represents a major challenge, intermetallic protective coatings have aroused increasing interest in the last years. In this work, a 10 μm thick intermetallic Ti–46Al–36Cr–4Zr (in at.-%) coating was applied on a TNB alloy using magnetron sputtering. This layer provided excellent oxidation protection up to 1000 °C. Microstructural changes in this coating during the high temperature exposure were extensively investigated using scanning and transmission electron microscopy. The coating developed a three-phase microstructure consisting of the hexagonal Laves-phase Ti(Cr, Al)2, the tetragonal Cr2 Al phase and the cubic τ -TiAl3 phase. After long-term exposure the three-phase microstructure changed to a two-phase microstructure of the hexagonal α 2 -Ti3 Al phase and an orthorhombic body-centred phase, whose crystal structure has not yet been definitely identified. On the coating, a thin protective alumina scale formed. Applying this intermetallic layer as bond coat, thermal barrier coatings (TBCs) of yttria partially stabilized zirconia were deposited on γ -TiAl based TNB samples using electron-beam physical vapour deposition. The results of cyclic oxidation testing (1 h at elevated temperature, 10 min. cooling at ambient temperature) revealed a TBC lifetime of more than 1000 h of cyclic exposure to air at 1000 °C. The ceramic topcoat exhibited an excellent adhesion to the thermally grown alumina scale which contained fine ZrO2 precipitates.